Development of a Zika Virus Infection Model in Cynomolgus Macaques - Koide, Fusataka; Goebel, Scott; Snyder, Beth; Walters, Kevin B.; Gast, Alison; Hagelin, Kimberly; Kalkeri, Raj; Rayner, Jonathan (Frontiers in Microbiology, 2016)
Limited availability of Indian rhesus macaques (IRM) is a bottleneck to study Zika virus (ZIKV) pathogenesis and evaluation of appropriate control measures in non-human primates. To address these issues, we report here the Mauritian cynomolgus macaque (MCM) model for ZIKV infection. In brief, six MCMs (seronegative for dengue and ZIKV) were subdivided into 3 cohorts with a male and female each and challenged with different doses of Asian [PRVABC59 (Puerto Rico) or FSS13025 (Cambodia)] or African (IBH30656) lineage ZIKV isolates. Clinical signs were monitored; and biological fluids (serum, saliva and urine) and tissues (testes and brain) were assessed for viral load by quantitative RT-PCR and neutralizing antibodies (Nab) by 50% Plaque Reduction Neutralization Test (PRNT50) at various times post infection (p.i). PRVABC59 induced viremia detectable up to day 10, with peak viral load at 2 to 3 days p.i. An intermittent viremia spike was observed on day 30 with titers reaching 2.5 ×103 genomes/mL. Moderate viral load was observed in testes, urine and saliva. In contrast, FSS13025 induced viremia lasting only up to 6 days and detectable viral loads in testes but not in urine and saliva. Recurrent viremia was detected but at lower titers compare to PRVABC59. Challenge with either PRVABC59 or FSS13025 resulted in 100% seroconversion; with mean PRNT50 titers ranging from 597 to 5179. IBH30656 failed to establish infection in MCM suggesting that MCM are susceptible to infection with ZIKV isolates of the Asian lineage but not from Africa. Due to the similarity of biphasic viremia and Nab responses between MCM and IRM models, MCM could be a suitable alternative for evaluation of ZIKV vaccine and therapeutic candidates.